English as a Lingua Franca in Multinational Corporations: A Case Study of Everyday Communication - Ryzhkova, Vera (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2018)
Tato bakalářská práce vysvětluje problematiku anglického jazyka jako lingua franca a jeho využití v každodenní komunikaci v nadnárodních společnostech. Práce sestává z teoretické a praktické části. První část popisuje status anglického jazyka jako celosvětového jazyka a jeho využití v globálním rozsahu. Pomocí Kachrova modelu také popisuje současnou pozici anglického jazyka ve světě. Druhá část se věnuje praktickému využití anglického jazyka jako lingua franca v mezinárodních společnostech a zvažuje tři z nejrozšířenějších žánrů obchodní komunikace. Veškerý analyzovaný materiál byl použit ze zdrojů interní komunikace v nejmenované mezinárodní společnosti

This bachelor’s thesis explains a phenomenon of English language as a lingua franca and its use in everyday communication in multinational corporations. The thesis consists of theoretical and practical parts. The first part describes the status of English as a global language and its use worldwide. It also explains the current position of English in the world based on the Kachru model of spread of English. The second part is devoted to practical use of English as a lingua franca in multinational corporations and considers three of the most popular genres of business communication. All analyzed materials are taken from internal communication within one multinational corporation.
English as a Lingua Franca in Multinational Corporations: A Case Study of Everyday Communication
Keywords: Angličtina; lingua franca; jazyk; obchodní angličtina; globalizace; obchodní komunikace; model Kachru; obchodní email; chat.; English; language; business language; lingua franca; Kachru model; global language; international language; globalization; business email; internal chat; chat communication.